Breastfeeding as Activism: Moving from Oppression to Emancipation - Jennifer L. Pemberton (Adult Education Research Conference, 2014)
Women have a long history of oppression. Despite making great strides towards equality, some mothers find their experience of breastfeeding oppressive. Mothers who experience oppression related to breastfeeding may become emancipated and engage in breastfeeding activism.